2010
DOI: 10.1097/bsd.0b013e3181b11d9f
|View full text |Cite
|
Sign up to set email alerts
|

Management of Type II Odontoid Fractures in the Geriatric Population

Abstract: Patients treated nonoperatively in rigid collar seem to have an overall favorable outcome. A well-designed prospective study, to compare the outcomes of surgical intervention with nonsurgical management of Type II odontoid in elderly is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 13 publications
0
18
0
3
Order By: Relevance
“…Omeis et al reported a 30.7% odontoid healing rate with posterior C1-2 surgery and a 37.5% healing rate with anterior odontoid screw fixation in the elderly population [18]. Chaudhary et al reported 87% fracture union after surgical treatment and 66% union with cervical collar treatment [2]. Osti et al report 29.0 and 8.6% morbidity and mortality in geriatric patients following anterior screw fixation of type II odontoid fractures [30].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Omeis et al reported a 30.7% odontoid healing rate with posterior C1-2 surgery and a 37.5% healing rate with anterior odontoid screw fixation in the elderly population [18]. Chaudhary et al reported 87% fracture union after surgical treatment and 66% union with cervical collar treatment [2]. Osti et al report 29.0 and 8.6% morbidity and mortality in geriatric patients following anterior screw fixation of type II odontoid fractures [30].…”
Section: Discussionmentioning
confidence: 97%
“…High rates of morbidity and mortality have been published with the surgical treatment of geriatric odontoid fractures [1][2][3]. [29] External immobilization with a collar has had inconsistent reported results [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 98%
“…atlantoaxial motion (8,9). In recent years, there has been an increasing tendency toward using anterior screw fixation in management of type II odontoid fractures (11).…”
Section: Mashhadinezhad H Et Al: Clinical Results Of Surgical Managementioning
confidence: 99%
“…Quatre études ont utilisé le score American Society of Anesthesiologists (ASA) [18,20,26,37], l'index de comorbidité de Charlson (CCI) [36] et le Cumulative Illness Rating Scale for Geriatrics (CIRS-G) [30]. Trois études renseignaient le nombre moyen de comorbidité par patient sans utiliser de score reconnu [21,34,38].…”
Section: Caractéristiques Des éTudesunclassified
“…Le vissage antérieur était la technique chirurgicale la plus représentée (75 %), et le collier cervical rigide était le type de contention orthopédique le plus représenté (65 %). Quatorze études rapportaient les critères de choix entre traitement chirurgical ou orthopédique [15,[17][18][19][20]22,23,25,[28][29][30][31]37,38]. Les trois arguments les plus fréquents étaient le nombre de comorbidités ou le statut ASA (six études sur 14), le choix du patient et/ou du chirurgien (six études sur 14) ainsi que les caracté-ristiques de la fracture (sept études sur 14).…”
Section: Caractéristiques Des éTudesunclassified